2022
DOI: 10.1186/s13104-022-06153-6
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of mayaro virus and coinfection with chikungunya during an outbreak in the state of Tocantins/Brazil

Abstract: Objective To perform a molecular screening to detect infections by the mayaro virus and possible coinfections with Chikungunya during an outbreak in the state of Tocantins/Brazil in 2017. Results Of a total 102 samples analyzed in this study, 6 cases were identified with simultaneous infection between mayaro and chikungunya viruses (5.88%). In these 6 samples, the mean Cycle threshold (Ct) for CHIKV was 26.87 (SD ± 10.54) and for MAYV was 29.58 (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
4
0
3
Order By: Relevance
“…MAYV is endemic to the Amazon region. An epidemiological study between 1955 and 2019 reported 1304 cases of MAYV infection in Brazil, with 1142 cases described only in the northern region [ 4 ], which includes the states of Pará, Amazonas [ 35 ], and Tocantins [ 36 ]. Ma.…”
Section: Discussionmentioning
confidence: 99%
“…MAYV is endemic to the Amazon region. An epidemiological study between 1955 and 2019 reported 1304 cases of MAYV infection in Brazil, with 1142 cases described only in the northern region [ 4 ], which includes the states of Pará, Amazonas [ 35 ], and Tocantins [ 36 ]. Ma.…”
Section: Discussionmentioning
confidence: 99%
“…With the spread of arboviruses [ 8 , 17 ] and the increase in human cases, there have been a growing number of patients presenting co-infection combinations of CHIKV, DENV and ZIKV [ 18 ] and recently reports of MAYV with DENV [ 19 ], CHIKV [ 20 , 21 ] and ZIKV [ 22 ]. While the observations of multiple infections in same patients indicate that Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Due to co-circulation with other arboviruses, clinical disease similarity, and alphavirus cross-reactivity, these infections can also be difficult to diagnose as differentiating diagnostics are limited. There are incidences of arboviral co-infections, including reports of MAYV and CHIKV co-infection [ 32 ] and ex vivo superinfection with MAYV and Zika (ZIKV) [ 17 ]. Co-infections with non-arboviruses like HIV have also been reported, but little research has been done to investigate the interplay of these co-infections or consequence of pre-existing immunodeficiency [ 33 ].…”
Section: Introductionmentioning
confidence: 99%